Space-Time Block Coded Reconfigurable Intelligent Surface-Based Received Spatial Modulation - Bayar, Ferhat; Salan, Onur; Ilhan, Haci; Aydin, Erdogan (IEEE COMPUTER SOC, 2024)
Reconfigurable intelligent surface (RIS) structures reflect incident signals by adjusting phase adaptively according to the channel condition during transmission to increase signal quality at the receiver. Spatial modulation (SM) technique is a potential candidate for future energy-efficient wireless communications due to its ability to provide better throughput, low-cost implementation, and good error performance. Also, Alamouti's space-time block coding (ASBC) is an important space and time coding technique for the diversity gain and simplified maximum likelihood (ML) detection. In this paper, we propose the RIS-assisted received spatial modulation (RSM) scheme with ASBC, namely RIS-RSM-ASBC, for next-generation wireless networks. The RIS in the proposed system model is separated into two parts, each used as an access point (AP) to transmit its Alamouti coded information while reflecting passive signals to the selected receive antenna. We design the optimal ML detector for the proposed RIS-RSM-ASBC scheme. Furthermore, we present the greedy detector (GD) to reduce the complexity of the ML detector. Extensive computer simulations are performed to corroborate theoretical derivations. The results show that the RIS-RSM-ASBC system is highly reliable and provides data rate enhancement compared to traditional RIS-assisted transmit SM (RIS-TSM), RIS-assisted transmit quadrature SM (RIS-TQSM), RIS-assisted received SM (RIS-RSM), RIS-assisted transmit space shift keying with ASBC (RIS-TSSK-ASBC), and RIS-assisted TSSK with Vertical-Bell Laboratories Layered Space-Time (RIS-TSSK-VBLAST) schemes.
Keywords: Modulation; Reconfigurable intelligent surfaces; Receiving antennas; MIMO communication; Detectors; Wireless communication; Indexes; Space time block coding; Alamouti's scheme; performance analysis; reconfigurable intelligent surface; spatial modulation; maximum likelihood; greedy detector; ASSISTED WIRELESS COMMUNICATIONS; CHANNEL ESTIMATION; INDEX-MODULATION; MIMO; PARADIGM; Computer Science; Telecommunications